Dry matter accumulation and partitioning in three varieties of amaranth - Nieto-Flores, Jose Bernardo; Barrales-Domínguez, José Sergio; Trejo-Téllez, Libia Iris; Gómez-Merino, Fernando Carlos (Revista Mexicana de Ciencias Agrícolas, 2025)
The revaluation of amaranth crops has a significant boom as a food of great value in human nutrition and a greater presence in the diet of the Mexican population and other countries. This study aimed to determine the dynamics of dry matter accumulation and partitioning by morphological organ in three varieties of amaranth (Amaranthus hypochondriacus L.): Areli, Diego and PQ2. An experiment was established in a completely randomized experimental design with four replications, under rainfed field conditions in the experimental field of Phytotechnics of the Chapingo Autonomous University, during the spring-summer cycle of 2023. From day 21 after the emergence, 17 whole plant samplings were performed every seven days, divided by organs and dried for the determination of dry biomass. The data were subjected to an analysis of variance (α= 0.05) and a comparison of means test (Tukey, α= 0.05). Of the total dry biomass, roots accounted for about 11%, stems ranged from 43 to 60%, and leaves made up about 32% of the total. Dry grain biomass accounted for about 11.2, 17.2 and 19% of total dry biomass in Areli, Diego and PQ2, respectively. Statistically significant differences were observed in the development of the three varieties. Diego and PQ2 showed greater accumulation of dry matter compared to Areli, under limited soil moisture conditions caused by low precipitation during the cycle.
Keywords: Amaranthaceae; grain yield; pseudocereal; total biomass